Incidence of some chronic musculoskeletal side-effects in the 335 veteran with bilateral lower limb amputation - K. Azma; H. seddigh (Afarand Scholarly Publishing Institute, 2010)
Background: Bilateral lower limb amputation in any level causes outbreak of some injuries and secondary side-effects in musculoskeletal system and depending on the level of dissection it involves lower limb stump including the upper limbs. Furthermore, the incidence of these side-effects varies depending on using any accessory equipment. Purpose :While lower extremities carry all the weight of body and consequently, the presence of lower limbs is crucial for movement and the general performance of body, the increase in the incidence of side-effects originated from amputation lowers the abilities of the person. Therefore, the information about the incidence of side-effects increases the ability of prevention and subsequently, Functional Independence Measure. Method & materials :Our study is a Cross Sectional type and the sampling was based on the convenient method. In this study, 335 people including 327 men and 8 women were chosen and 97% of them had more than 70% of disability. The average age was 42 6/3. They were invited from 26 provinces and several side-effects such as pain in upper limbs and lower stump , spinal deformity and tendinitis were evaluated. Results:The investigations showed that knee pain (left: 8.1%, right: 7.5%) were the most incident pain in lower limb and shoulder pain (left: 9.6%, right: 9%) were the most incident juncture pain in upper limbs in disabled people with both lower limb amputation . Moreover, most of the disabled (52.5%) suffered from pain in lumbosacral vertebra. The most incident tendinitis in upper limbs were biceps tendinitis (right: 4.8%, left: 4.2%) and lateral epicondylitis (right: 3.3%, left: 3.3%) respectively and Ischial bursitis (right: 3%, left: 3.3%) was the most incident bursa in lower limbs. Conclusion:The information about the incidence of side-effects increases the ability of prevention and elevates Functional Independence Measure. In addition, the technical orthopedist will have better and more scientific view of their drawbacks and problems by employing the accurate knowledge they have about these side-effects and will try for improve technical and functional performance of their products.